Phylogeny and phylogeography of Barbonymus schwanenfeldii (Cyprinidae) from Malaysia inferred using partial cytochrome b mtDNA gene - Kamarudin, Kamarul Rahim; Esa, Yuzine (Institute for Tropical Biology and Conservation, Universiti Malaysia Sabah, 2009)
A study on the genetic variation of Barbonymus schwanenfeldii (Bleeker) populations from Malaysia was done using partial sequencing of cytochrome b mtDNA gene. Samples were collected from various localities in Peninsular Malaysia, Sarawak and Sabah, including the Indonesian (Kalimantan) type of B. schwanenfeldii from Kapit, Sarawak. Phylogenetic relationship inferred using neighbour joining, maximum likelihood and maximum parsimony methods generally divided samples into two major groups, consistent with their geographic origin: one widespread group consisted of B. schwanenfeldii (locally known as Lampam sungai) from Peninsular Malaysia while another particular group clustered B. schwanenfeldii (locally known as Tengadak) from Sarawak. Within the Peninsular Malaysia, our current data supported the validation of two main divisions: central and southern division (CS; consisting of Serting River, Muar River and Padang Piol, Jerantut, Pahang) and north west and north east division (NWE; consisting of Pulau Banding, Perak and Tasik Timah Tasoh, Perlis). The low distance values between haplotype sequences (0.00 to 1.01) and low Phylogeny and phylogeography of Barbonymus schwanenfeldii (Cyprinidae) from Malaysia inferred using partial cytochrome b mtDNA gene nucleotide diversity, Pi (0.005) showed a very close genetic relationship between samples, enforcing their taxonomic validation as belonging to a single taxon. However, the low level of gene flow (Nm = 0.07) and high population structuring (Fst = 0.88) between Peninsular Malaysia and Sarawak could be correlated with the separation of Borneo Island from mainland Peninsular during last Pleistocene Epoch.